Impact of Psychological Empowerment (PE) on Job Engagement (JE) among the Employees of ETUST-Tebessa - Chouki Djeddi; Khatima Louati; Bachir Kaoudja (Dirassat Journal Economic Issue, 2021)
The present study aims to identify the effect of psychological empowerment (PE) in its dimensions (meaning, competence, self-determination and impact) on the job Engagement (JE) of ETUST employees of Tébessa. A questionnaire was distributed on a sample of (75) workers, with the use of (SPSS) and the (AMOS) programs. The study revealed some results  with  the  most  important  as  follows: the existence of a statistically significant effect of psychological empowerment, which explained (75.9%) the variation in the level of job Engagement, the researchers have found out that  there  is  a  statistically  significant  impact  of  two  dimensions  of  (PE): independence and impact on  (JE), and the study found a non-significant impact on the two dimensions: meaning and efficiency. Finally, the study suggested a number of important recommendations to improve the level of psychological empowerment in the institution under study, to enhance the job Engagement. Keywords:.psychological empowerment; Job Engagement; ETUST Tébessa